Asymptotic Stability for a Quasilinear Viscoelastic Equation with Nonlinear Damping and Memory (Journal of Partial Differential Equations, 2023)
This paper is concerned with the asymptotic behavior of a quasilinear viscoelastic equation with nonlinear damping and memory. Assuming that the kernel $μ (s)$ satisfies $$μ'(s)\le -k_1μ^m(s), \ 1\le m